Division on Investment and Enterprise : results and impact report - 2012- (UN New YorkUS, 2012)
Presents annual report on the work of Division of Investment and Enterprise. Reports on the continued achievements of the adoption of the strategic workplan guided by the results-based management approach.
Keywords: FOREIGN INVESTMENT